Green supply chain management: definition of criteria and selection of suppliers in the foundry sector - Stoco, Wanderson Henrique; Baldassin, Fernando; Oliveira, Maria Célia de (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose – This article aims to propose criteria for the selection of green suppliers in the foundry sector and select the best suppliers for the organization where researched, by applying the AHP method. Design/methodology/approach – An applied survey was carried out where specialists from the foundry sector were consulted and after the survey had been completed, criteria were defined to select green suppliers. Findings – Adopting the defined criteria and applying the Analytical Hierarchy Process (AHP) decision-making method, five suppliers were classified, with Environment, Health and Safety criteria being considered the most important according to the opinion of the experts consulted in this survey. Originality/Value – The study allows organizations to see the importance of the supplier selection process in the foundry sector, where worldwide concerns for the environment are increasingly present and environmental standards and regulations are strict. Keywords – Green supply chain. Supplier selection. AHP method.